PERISTILAHAN DALAM UPACARA ADAT NYABAKNG MASYARAKAT DAYAK BAKATI’ DESA SEGIRING KABUPATEN BENGKAYANG - Kastria, Nina; Salem, Laurensius; Patriantoro, Patriantoro (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe term of costum ceremony in Dayak Bakati? community at Segiring Village is seen from the inventory, the lexical meaning, and the cultural sense. The research method was descriptive linguistics. The research approach was semantic approach. The source of research was the speech of Dayak language Bakati? Segiring dialect spoken by native speakers of Segiring village, Tujuh Belas Subdistrict, Bengkayang Regency. The technique of research was interview, record, notebook, and documentation. The tool of data collection was voice recorder and notebook. Based on the research, the researcher collect 64 terms in the nyabakng ceremony. The data was obtained from the interview and recording process. The terms of the traditional ceremony in the study consisted of 12 tool terms, 48 material terms, 3 terms of offender, and 1 place term. The term of ceremony consist of two terms, 39 terms of monomorfemis (single word) and the 25 terms of phrases. The term in the costum ceremony has a 64 terms of lexical meaning, and 50 terms of cultural sense.Keywords: Terminology, Nyabakng traditional ceremony, Dayak Bakati?.